ТЕХНОЛОГИЯ ОПРЕДЕЛЕНИЯ КОЭФФИЦИЕНТА ТЕКУЩЕГО НЕФТЕНАСЫЩЕНИЯ ТЕРРИГЕННЫХ КОЛЛЕКТОРОВ - Белохин B.C.; Калмыков Г.А.; Коротков К.В.; Решетов Е.В.; Смирнов Д.Г. (My University, 2006)
Presented is a technology for processing nuclear logs acquired in cased, non-perforated wells. The technology allows determine mineral composition of reservoir matrix, flow properties and oil saturation index of reservoirs. Oil saturation is found basically from C/O-logs which are processed by decomposing measured gamma-ray spectra into elementary spectra computed by Monte-Carlo method. Next geophysical characteristics of reservoir are converted to mineral and componential composition using a system of petrophysical equations built based on the core analysis. Reliability of results is demonstrated by comparing estimates of oil saturation produced by this technology versus logging and core results acquired in an open hole not involved into production.
Keywords: 553.98.061.4:539.217